Strategi Tabligh Kegiatan "Ahadan" Dalam Membina Akhlak Santri dan Masyarakat - Albanajib, Rafiq; Muklis, Atjep; Rahman, Encep Taufik (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2023)
This study aims to determine the planning, methods used and concrete results regarding the tabligh strategy used by the Al-Mushlih Cibalong Islamic Boarding School in the â€œahadanâ€ activity in fostering the morals of students and the community. The theory of this research is Harold Lasswel about communication planning and communication planning from Middleton that communication strategy is a combination of several important elements of communication. The research method used is qualitative research method. The results of this study are the tabligh strategy used in the â€œahadanâ€ activity is a method that refers to Q.S An-Nahl verse 25, namely the method of bil-hikmah, ma'udzhatil hasanah and mujadallah and planning in the form of a good relationship approach (chemistry) on the part of the pesantren. The concrete results of â€œahadanâ€ activities are widely felt by the congregation, especially in moral development.